The mile high magic pyramid - Anastasiou,A; Borsten,L; Duff,MJ; Marrani,A; Nagy,S; Zoccali,M (American Mathematical Society, 2019)
Using a unified formulation of N=1,2,4,8, super Yang-Mills theories in D=3 spacetime dimensions with fields valued respectively in R,C,H,O, it was shown that tensoring left and right multiplets yields a Freudenthal magic square of D=3 supergravities. When tied in with the more familiar R,C,H,O description of super Yang-Mills in D=3,4,6,10 this results in a magic pyramid of supergravities: the known 4×4 magic square at the base in D=3, a 3×3 square in D=4, a 2×2 square in D=6 and Type II supergravity at the apex in D=10.